Monitoring and follow-up to Project No. 891 "Strengthened secondary education and greater access to tertiary education" and its budget within the District Development Plan "Bogotá Humana 2012-2016" (2014)
The main objective of this document is to assess the budget distribution made by Bogotá’s Secretariat of Education directed to public schools that belong to the Project 891 from its creation. This project has been developed within the Development Plan of Bogotá’s Administration “Bogotá Humana 2012-2016”. Regarding this objective, it is important to analyze the investments made by this project taking into account its objectives, goals and purposes. Thus, it is necessary to assess the current status, transformation and implementation of strategies from budgetary, academic, pedagogical and institutional scopes which have allowed the inclusion of more schools to the Strengthened Secondary Education and Optional 12th Degree, since this fact will provide analysis and assessment tools that can be considered an element of strengthening for Bogotá’s secondary education and its homologation in tertiary education.